Factors of s-commerce influencing trust & purchase intention - Pothong, Chutada; Sathitwiriyawong, Chanboon (My University, 2017)
This paper aims to study factors influencing trust and purchase intention on the Internet, develop model of trust and purchase intention by empirical data, and analyze path of antecedents influencing purchase intention. This study identifies the factors proposed in the existing social commerce constructs: Recommendation and referrals, rating and reviews, forums and communities, together with three additional important factors in online environments to get comprehensive results comprising security concerns, communication, and word of mouth. It has been found that the four investigated factors: Recommendation and referrals, rating and reviews, communication, and WOM, have positive effects on both trust and purchase intention. The rest of the investigated factors: forums and communities, and security concerns have positive effects specific to trust. The results also indicate that the more consumers trust an s-commerce, the more likely they are to exhibit purchase intention.
Keywords: Purchase intention; Social commerce; Social commerce constructs; TAM; TRA; Trust